A Bioinspired Swimming and Walking Hydrogel Driven by Light‐Controlled Local Density. Issue 6 (15th May 2015) - Wang, Lei; Liu, Yang; Cheng, Yao; Cui, Xiuguo; Lian, Huiqin; Liang, Yongri; Chen, Fei; Wang, Hao; Guo, Wenli; Li, Hangquan; Zhu, Meifang; Ihara, Hirotaka
<x xml:space="preserve">Abstract</x> A hydrogel exhibits a real‐time depth‐controllable swimming motion via light‐mediated modulation of local density to mimic the volume changes found in the bladders of fish. Moreover, other motions, e.g., rolling, somersaulting, and bipedal‐like walking, can also be realized by designing or combining gel shapes, and the location of light.